A Mosaic of Creativity in Occupational Therapy - Molly Bathje MS, OTR/L (Scholarworks @ WMU, 2014)
Martha Branson-Banks, OT, provided the cover art for the summer 2014 issue of the Open Journal of Occupational Therapy. The piece is titled "Garden with thanks to Klimt" and is one of several mosaic art pieces in her collection of works. She created the piece with art glass and resin on an abandoned door. Her use of a repurposed door represents her belief in the capacity for transformation and beauty within each individual she has treated and taught throughout her career. Martha's work as an occupational therapist, educator, and artist reminds us of the foundational beliefs of the occupational therapy profession, including the benefits of engagement in meaningful and creative activities.